PENGARUH GREEN MARKETING DALAM SOSIALISASI “DIET KANTONG PLASTIK” TERHADAP KEPUTUSAN PEMBELIAN PADA PRODUK ECO BAG (TAS BELANJA RAMAH LINGKUNGAN) ALFAMART MELALUI MINAT BELI SEBAGAI VARIABEL INTERVENING (Studi pada Konsumen Alfamart di Kabupaten Pati) - Aziz Zulkifli Utomo; Bambang Munas Dwiyanto (Diponegoro Journal of Management, 2022)
This study aims to analyze the effect of green marketing to attract buying interest and to persuade people to make purchasing decisions on Alfamart Eco Bag products as a substitute for plastic bags. The population used in this study is the people of Pati Regency who have shopped at Alfamart. The number of samples used in this study were 106 respondents who had been selected by purposive sampling technique and collected using a questionnaire method that had been tested for validity and reliability. This research uses Structural Equation Modeling (SEM) analysis technique with AMOS analysis tool and Sobel test which is used to answer the research hypothesis. The results showed that green marketing has a positive and significant impact on purchasing decisions on Eco Bag products. In addition, green marketing has a positive and significant influence on buying interest. While buying interest has a positive and significant influence on purchasing decisions on Eco Bag products. In this case, buying interest is able to have a significant effect in mediating the influence of green marketing on purchasing decisions.